Numerical Study on Failure Mechanism of Rock Slope Formed by Mudstone at Girdu, Pakistan - Zulkifl Ahmed; Sumra Yousuf; Muhammad Rizwan; Muhammad Yousaf Raza Taseer; Muhammad Qasim Sultan; Mahwish Zahra; Anum Aleha (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Failure analysis of rock slope is a core topic in rock mechanics and geotechnical engineering. This paper simulates the failure mechanism of a rock slope formed by mudstone at Girdu, Pakistan. Initially, site surveys and laboratory experiments were carried out to measure slope geometry and input shear strength properties of the material. The geotechnical structure and model analyzing computer program (GeoSMA3D) was used to determine the stability of the main slippery blocks. A shear strength reduction method was selected in a three-dimensional distinct element code (3DEC) to examine the failure mechanism, the factor of safety (FS), shear strain concentration, and displacement of slope at various monitoring points. Furthermore, the effect of the rock slippery block, slope angle, and slope height on failure modes of slope were assessed. The present results showed that the studied section is prone to big planer failure at both maximum and minimum strength properties. Slope angle and height significantly influenced the failure characteristics of rock slope . It is inferred that these parameters must be precisely considered during slope reinforcement design.